2006
DOI: 10.1186/1471-2458-6-299
|View full text |Cite
|
Sign up to set email alerts
|

Aiming to increase birth weight: a randomised trial of pre-pregnancy information, advice and counselling in inner-urban Melbourne

Abstract: BackgroundIn the 1980s there was substantial interest in early pregnancy and pre-pregnancy interventions to increase birth weight and reduce preterm birth. We developed an inter-pregnancy intervention, implemented in a randomised controlled trial, to be provided by midwives at home soon after women's first birth.MethodsMCH nurses invited women to take part during their home visit to new mothers. Women's contact details, with their permission, were passed to the study midwife. She had a randomisation schedule t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 30 publications
0
77
0
Order By: Relevance
“…However, in this review we have only been able to include results from four trials (Floyd 2007;Lumley 2006;Robbins 2005;Velott 2008). Two studies did not report findings for the whole sample according to group allocation, but rather for non-random subsets.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in this review we have only been able to include results from four trials (Floyd 2007;Lumley 2006;Robbins 2005;Velott 2008). Two studies did not report findings for the whole sample according to group allocation, but rather for non-random subsets.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…While blinding outcome assessors is possible, participants may disclose group allocation or case notes may reveal it, so blinding may be difficult to achieve in practice. In three of the studies it was not stated whether there was any attempt to blind outcome assessors (Floyd 2007;Lumley 2006;Robbins 2005). In the Pennsylvania study (Velott 2008), it was reported that assessors carrying out physical assessments were blind to group allocation.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Parenting attitude [21] Responsibility [21] Parent's sense of competence [21] Social competence [18,19] N/A Providing pre-pregnancy information [14,[18][19][20]22] Casaerean section rate [22] Rate of spontaneous onset of labour [22] Apgar scores [22] Birth weight [22] Gestational age [22] Prematurity [22] Information about maternal self-care (e.g. Nutrition, physical activity) [18,19] N/A N/A Modifying behaviors [18,19] Smoking behavior [18,19] Caregiver self-sufficiency [23] Episodes of malaria treated at community level [24] Symptom severity of asthma [23] Emergency department visit [23] Safety management [16,18,19] N/A HOME score [16] Intense home visit by developmental milestone Infant and toddlers Providing information of child nutrition and physical activity by developmental milestone [25,26] Infant weight gain [25] Introduction of solids [25] BMI [25] Eating habits (TV viewing time) [25] Intake of fruit and vegetables [25] Physical activity [25] Frequency of eating [25] processed meat [25] No continuous effect on BMI, physical activity, eating habit (3 years after intervention) [26]...…”
Section: 선정 논문의 질 평가mentioning
confidence: 99%